PENGARUH UKURAN PERUSAHAAN SERTA GOOD CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BEI TAHUN 2018-2021 - Ali Ridho Rozy; -, Yunita Fitria (Jurnal Ilmu Akuntansi, 2024)
This research aims to study and analyze the influence of firm size and good corporate governance on earnings management. The sample in this study consisted of twenty six manufacturing company in various industrial sectors listed on the indonesian stock exchange. The type of data used is quantitative data with data collection methods in the form of documentation methods. The data used in this research is secondary data sourced from company financial reports. The analytical tool used in this research is the SPSS version 25 program using multiple linear regression analysis with classical assumption tests. The results of this research show that firm size and audit committee have a significant and positive effect on earnings management, independent board of commissioners has a significant and negative effect on earnings management and institutional ownership has an insignificant and positive effect on earnings management.